RANCANG BANGUN APLIKASI ANTRIAN BAP PASPOR WNI BERBASIS WEBSITE MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) PADA KANTOR IMIGRASI KELAS I TPI CIREBON - Aji, M.Bayu Krisna; Karunia, Ferdyan Samuel; Hilmy, Muhadzib Rezki; Berlian, Theresya; Trinata, Cakra (TEMATICS: Technology Management and Informatics Research Journals, 2024)
Abstract. The queue application for the Investigation Report (IR) of Indonesian Passports is a web-based software designed to enhance the efficiency of immigration services at the Class I Immigration Office of TPI Cirebon. This application allows applicants to book queues online, select appropriate service times, and access information related to BAP requirements, including cases of lost, damaged, or altered passport data. By automating processes that were previously manual, this application reduces waiting times and improves customer satisfaction. This study employs the Rapid Application Development (RAD) methodology, which enables the rapid and responsive development of applications according to user needs. The RAD method involves iterative phases, including requirements analysis, system design, development, and implementation, allowing for adjustments and improvements throughout the development process. The outcome of this research is a prototype application that enables BAP applicants to book queues online, choose flexible service times, and access detailed information about the BAP process and requirements. The application was tested using usability testing and blackbox testing methods to ensure that all features function properly and meet user needs. The implementation of this application is expected to provide an effective solution for improving the quality of immigration services in the digital era.